Answer:
D. g(x) is a reflection of f(x) over the x-axis.
Explanation:
Given
f(x) = 2x²
g(x) = -2x²
Required
Determine the difference between f(x) and g(x)
Start by expanding g(x)
g(x) = -2x²
g(x) = -1 * 2x²
Substitute 2x² for f(x)
g(x) = -1 * f(x)
g(x) = -f(x)
Using the format (x,y):
Take for instance x = 2
f(x) = 2x² = 2 * 2² = 2 * 4 = 8
This means (x,y) = (2,8)
g(x) = -f(x)= -8
This means that (2,-8)
Notice that only the y value changed in both cases from 8 to -8
From the above expression, g(x) = -f(x) and illustration of when x = 2
This implies that g(x) is a reflection of f(x) along the x axis..
From the list of given options, the correct answer is D.